2020
DOI: 10.3390/ijms21030878
|View full text |Cite
|
Sign up to set email alerts
|

The miRNAs Role in Melanoma and in Its Resistance to Therapy

Abstract: Melanoma is the less common but the most malignant skin cancer. Since the survival rate of melanoma metastasis is about 10–15%, many different studies have been carried out in order to find a more effective treatment. Although the development of target-based therapies and immunotherapeutic strategies has improved chances for patient survival, melanoma treatment still remains a big challenge for oncologists. Here, we collect recent data about the emerging role of melanoma-associated microRNAs (miRNAs) currently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 237 publications
(199 reference statements)
0
38
0
Order By: Relevance
“…25,26 Interestingly, accumulating studies demonstrated the enrollment of miRNAs in the oncogenesis and progression of melanoma. [27][28][29] MiRNAs may perform tumor-suppressing or tumor-promoting activities in melanoma, and are implicated in the regulation of multiple aggressive processes. 30,31 Hence, studying the expression and roles of miRNAs in melanoma my highlight potential targets for managing melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Interestingly, accumulating studies demonstrated the enrollment of miRNAs in the oncogenesis and progression of melanoma. [27][28][29] MiRNAs may perform tumor-suppressing or tumor-promoting activities in melanoma, and are implicated in the regulation of multiple aggressive processes. 30,31 Hence, studying the expression and roles of miRNAs in melanoma my highlight potential targets for managing melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is also important to determine whether elevated miRs regulate MAPK pathway. In a previous study, high levels of miR-125b-5p were shown to be associated with Vemurafenib (BRAF inhibitor) resistance [ 47 , 48 ]. Accordingly, we observed that miR-125b was elevated in CII non-responder patients, but decreased in responding patients to CII ( Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The role of miRNAs in melanoma progression is very tangled, therefore excellent reviews can be consulted here: [ 28 , 35 , 36 , 37 ]. In principle, miRNAs influence the evolution of melanoma to secondary sites mainly by: (A) regulating the expression of MITF-M , an essential melanocyte-and melanoma-specific transcription factor that operates as a “switch” in the establishment of an invasive or proliferative phenotype; (B) remodelling the extracellular matrix (ECM); (C) promoting epithelial-to-mesenchymal transition (EMT) and its reverse, mesenchymal-to-epithelial transition (MET); and (D) preparing the formation of the pre-metastatic niche [ 28 , 36 , 38 , 39 , 40 ] ( Figure 1 ).…”
Section: Micrornas Modulate Melanoma Invasion and Metastasismentioning
confidence: 99%
“…The same issue arises with the use of immunotherapy [ 27 ]. The role of ncRNAs in the development of melanoma drug resistance has been questioned and while the contribution of miRNAs is well studied [ 37 ], the role of lncRNAs in such resistance is still largely unknown.…”
Section: Non-coding Rnas In Drug Resistancementioning
confidence: 99%